The Influence of Teacher Creativity on the Learning Motivation of Public Elementary School Students in Tomohon City - Margareta Oktavia Sumilat; Joulanda A.M. Rawis; Jeffry S.J. Lengkong; Orbanus Naharia (Peneliti.net, 2026)
This study was conducted to examine the influence of teacher creativity on the learning motivation of public elementary school students in Tomohon City using the Structural Equation Modeling (SEM) approach. The research applied a quantitative explanatory design. The population included all fifth- and sixth-grade students from 21 public elementary schools in Tomohon City. Using the Lemeshow formula with a 95% confidence level, the study obtained a sample of 384 respondents. Data were gathered through a Likert-scale questionnaire containing 8 indicators of teacher creativity and 10 indicators of learning motivation. The data were analyzed using AMOS through descriptive statistics, measurement model analysis, and structural model evaluation. The results showed that teacher creativity was categorized as very high, with an average score of 4.444, while students’ learning motivation was also classified as very high, with a mean score of 4.392. In addition, the SEM analysis demonstrated that the proposed model achieved a good fit. The findings further confirmed that teacher creativity had a positive and significant influence on students’ learning motivation, as indicated by a standardized path coefficient of 0.471 and a significance level of p < 0.001. Therefore, the study concludes that enhancing teacher creativity can effectively increase students’ learning motivation